P-146 A SYSTEMATIC REVIEW OF IMAGING MARKERS FOR HIATUS HERNIA OUTCOMES. (13th October 2022) - Wei, R; Gilmore, K; Findlay, J; Spellar, K
Abstract: Hiatus hernia repair is a common operation with considerable variation in anatomy and technique. At present there are very few predictors of post-operative outcomes. Certain imaging characteristics may help in operative planning and predicting outcomes. The aim of this systematic review is to identify possible radiological markers associated with clinical outcomes in hiatal hernia repair. A literature search was performed on the 7th December 2021 in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses and Meta-analysis Of Observational Studies in Epidemiology guidelines of the PubMed, EMBASE and Cochrane Central Register of Controlled Trials using the following search term: ((hiatus) OR (paraesophageal)) AND (hernia) AND ((computed tomography) OR (CT) OR (imaging) OR (contrast) OR (swallow) OR (magnetic resonance) OR (ultrasound)). Inclusion criteria were studies (any design) testing the association of a radiological marker with any clinical outcome (either operative or non-operative) of hiatus hernia management. Exclusion criteria were case reports, non-English articles, non-human articles. Articles were screened by 2/3 authors on the basis of title and abstract. Full text articles were then retrieved for detailed analysis. Any disagreement was resolved by consultation with a 3rd/4th author. Initial search identified 2768 papers, 9 of which were retrieved for full paper evaluation. Preliminary review of the literature suggests that hernia recurrence is correlated with increased hernia size, although patients tend to be asymptomatic. Multidimensional CT can accurately measure hernia surface area and this could be useful in stratifying risk of re-herniation.